Developing Affective Communication Skills in a Clinical Laboratory Sciences Program at a Small Liberal Arts College. - SCHOELL, MATTHEW (Clinical Laboratory Science)
This study evaluated the ability of simulated laboratory activities to develop affective skills, especially oral communication. Surveys were administered to students at the start and end of a clinical chemistry laboratory course at Nazareth College, a primarily liberal arts college that is not attached to a major medical center. These students included both clinical laboratory science majors and non-majors. Survey questions asked students to use a Likert scale to score their preparedness to properly identify patients, verbally communicate critical results, and discuss preanalytical challenges that affect specimen integrity. During the course, students evaluated mock laboratory results and were required to orally discuss preanalytical and postanalytical issues with a volunteer role-playing as an emergency department physician. Data indicate statistically significant (p < 0.5) increases in mean scores, comparing surveys before and after the course. The smallest increase in mean scores was seen in preparedness to discuss preanalytic errors with health care team members (2.56 increased to 3.79), whereas the largest increase was seen in preparedness to orally report critical results (2.81 to 4.57). Based on these findings, it appears that the laboratory activities succeeded in boosting students' confidence and perceptions of preparedness to communicate successfully with health care team members.